Durian Marketing Efficiency in Durian Tourism Village in Sumber Agung - Wulandari, Dita; Qurniati, Rommy; Herwanti, Susni (Jurnal Sylva Lestari, 2018)
Regional Forestry Office of Lampung Province has declared Sumber Agung Village as a Durian Tourism Village. In order to encourage the durian tourism village as a center of durian marketing, it is necessary to conduct a research which aim to know the efficiency of durian marketing to support the durian tourism village. The analysis used in this study were including the analysis of marketing channels, market structure, market behavior and marketing margin. The research showed that there were 4 durian marketing channels in Sumber Agung Village and the most efficient channel was from farmer through retailer and to final consumer. According to the market structure, market behavior and uneven margin distribution, the durian marketing has not been efficient and tends to be oligopsony. Keywords: durian, efficiency, marketing, tourism village.